Spatio-temporal evolution and distribution characteristics of the high-quality development of China’s insurance industry - Heng Zhu; Bo Xiong; Meimei Tang (PLoS ONE, 2025)
This study, based on the criteria of “inclusiveness,” “sustainability,” and “internal-external structural coordination,” establishes an evaluative framework for appraising the high-quality development of the insurance sector. It systematically gauges the overarching high-quality developmental status of China’s insurance industry across regions. Employing non-parametric kernel density estimation, the Standard Deviation Ellipse, and spatial Markov chain, the investigation dynamically scrutinizes the national landscape of high-quality evolution within the insurance sector over the temporal spectrum. Furthermore, Moran’s index and Dagum’s Gini coefficient are harnessed to disentangle the spatial interdependence and heterogeneity characterizing the high-quality progression of the insurance industry among provinces. The findings disclose a pronounced regional development gap throughout China, surpassing intra-regional disparities and underscoring a notable concern of imbalance in regional insurance industry development. Despite the elevated development stature of the eastern region, substantial interprovincial differentials persist, exposing internal “inequities” within this region. In the central and western domains, although internal divergences in insurance industry development are gradually diminishing, the overall developmental benchmarks remain comparatively subdued.